2020
DOI: 10.3390/diagnostics10050265
|View full text |Cite|
|
Sign up to set email alerts
|

miR-196B-5P and miR-200B-3P Are Differentially Expressed in Medulloblastomas of Adults and Children

Abstract: Medulloblastoma is a highly aggressive brain tumor that typically affects children, while in adults it represents ~1% of all brain tumors. Little is known about microRNA expression profile of the rare adult medulloblastoma. The main aim of this study was to identify peculiar differences in microRNA expression between childhood and adult medulloblastoma. Medulloblastomas were profiled for microRNA expression using the Exiqon Human miRNome panel (I + II) analyzing 752 microRNAs in a training set of six adult and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 109 publications
0
3
0
Order By: Relevance
“…Zhang et al showed that miR-200b-3p was also upregulated in neonatal rat brains in the early stage following hypoxia-ischemic injury, and that its inhibition led to a diminished neuronal apoptotic rate [106]. Medulloblastomas exhibit differential expression of miR-200b-3p according to age, with adults presenting an overexpression compared to pediatric patients [107]. Furthermore, miR-200b-3p among other miRNAs was upregulated in patients with brain metastatic gastric adenocarcinomas when compared to patients with this cancer but without cerebral metastases [108].…”
Section: Mir-200b-3pmentioning
confidence: 99%
“…Zhang et al showed that miR-200b-3p was also upregulated in neonatal rat brains in the early stage following hypoxia-ischemic injury, and that its inhibition led to a diminished neuronal apoptotic rate [106]. Medulloblastomas exhibit differential expression of miR-200b-3p according to age, with adults presenting an overexpression compared to pediatric patients [107]. Furthermore, miR-200b-3p among other miRNAs was upregulated in patients with brain metastatic gastric adenocarcinomas when compared to patients with this cancer but without cerebral metastases [108].…”
Section: Mir-200b-3pmentioning
confidence: 99%
“…These differentially expressed miRNAs were expected to be key indicators for the identification of specific MB-associated markers. Visani et al (35) indicated that there were differences in miR-196B-5P and miR-200B-3P expression between adults and children. Their study suggested that miRNAs may be involved in the development of MB, but not in the differences noted in the biological responses of adults and children with MB.…”
Section: Mirnas In Mbmentioning
confidence: 99%
“…CRK and CRK-like, 2 cellular counterparts of viral oncogene v-Crk, are critically implicated in the tumor-forming process of tumor cells. 12 A recent study has identified CRK as an oncogene in Wilm’s tumor by enhancing cell invasion, migration and inducing mesenchymal-to-epithelial transition. 13 In light of those findings, we speculated that miR-215-5p might target CRK to affect the biological behaviors of cancer cells in Wilm’s tumor.…”
Section: Introductionmentioning
confidence: 99%